PERANCANGAN SISTEM INFORMASI PENJUALAN PRODUK INDUSTRI PLASTIK BERBASIS WEBSITE (STUDI KASUS CV CATUR NAGA UTAMA) - Ahmad Ghani Fadillah (2022)
CV Catur Naga Utama is a company or factory that produces plastic industrial products, having its address at Villa Mas Asri Housing Block C1 No4, Ciledug, Kec. Setu, Bekasi, West Java 17320 which produces plastic products such as bottles, spray bottles, drigens, cosmetic containers and others on a large scale with a vision of "Prioritizing Quality, Service and Customer Convenience". The system running on CV Catur Naga Utama is still manual and not well integrated so that in the business process there are still many shortcomings. It is difficult for customers to find the products they want so that the sales target at CV Catur Naga Utama is still stable and sometimes decreases, never significantly increasing. Therefore, the purpose of this research is to create a sales and ordering information system for this plastic industry product through the media website. The research method used is descriptive with a case study approach of CV Catur Naga Utama. The method used is structured, namely focusing on self and analysis of current and actual problems, then the data obtained in the process and compiled and then presented in an analytical explanation using analytical methods. Descriptive research is research that observes problems systematically and accurately against a fact and the nature of a particular object. In making this application using UML diagrams and using programming languages HTML, CSS, Java Script, PHP. The results of this study refer to the solution to a problem, namely by designing a sales and ordering information system, with this system it can help consumers find their needs and can also get information about what products are sold. Then customers can easily get the goods they want through orders that can be made through the website. To test this system is running well or not the author uses testing using the Blackbox method